GAMBARAN KEPATUHAN MAHASISWA KLINIK FAKULTAS KEDOKTERAN GIGI UNIVERSITAS SYIAH KUALA DALAM HAL PEMISAHAN LIMBAH MEDIS DAN NON-MEDIS - Cut Fera Novita; Poppy Andriany; Rico Dwianda Helmi (Dentistry Faculty, 2017)
Compliance in health behavior is the extent to which the condition of individual behavior in accordance with health standards. The waste generated by health care are medical waste and non-medical waste.The amount of medical waste originating from health facilities are expected to increase. Dental and Oral Hospital of Syiah Kuala University is the only oral and dental health services in Banda Aceh. Hospital operations which highly complex not only have a positive impact for society, but also allows a negative impact in the form environmental contamination and cross-infection diseases such as HIV / AIDS, hepatitis B and C due to the an incorrect disposal and management of waste. The aim of this study was to describe the compliance of clinical student Faculty of Dentistry of Syiah Kuala University in case of medical and non-medical waste separation. This is a descriptive research with cross sectional data collecting method. This research does not require the consent of the respondent. How to measure in this study is by given a score of 1 when the separation of medical waste is done and given a score of 0 if it is not done. Rate of compliance will be categorized in three categories: good 75%, medium = 56-74%, and bad 55%. Data were analyzed by descriptive and presented in tabular or graphical. The results showed that the compliance overview of clinical students Faculty of Dentistry Syiah Kuala University in case of medical and non-medical waste separation as follows; 28 people categorized as good (35%), 41 people categorized as medium (52%), and 10 people categorized as bad (13%). The conclusion of this study indicate the medium category, which amounted to 41 (52%).Keywords : Complience, clinical student, medical and non-medical waste separation.